Prospective longitudinal cohort study of uterine arteries Doppler in singleton pregnancies obtained by IVF/ICSI with oocyte donation or natural conception. Issue 11 (25th October 2020) - Cavoretto, P I; Farina, A; Miglio, R; Zamagni, G; Girardelli, S; Vanni, V S; Morano, D; Spinillo, S; Sartor, F; Candiani, M
Abstract: STUDY QUESTION: Do uterine arteries Doppler studies show different pulsatility index (UtA-PI) measurements in IVF/ICSI pregnancies with oocyte donation (OD) as compared to natural conceptions? SUMMARY ANSWER: In IVF/ICSI pregnancies with OD, UtA-PI is reduced by an average of about 40% as compared to pregnancies with natural conception. WHAT IS KNOWN ALREADY: OD pregnancies present worse pregnancy outcomes as compared to natural conception, particularly for increased incidence of pre-eclampsia (PE). Recent evidence shows that IVF/ICSI pregnancies with frozen blastocyst transfer also present higher prevalence of PE and 15% lower UtA-PI as compared to pregnancies after fresh blastocyst transfers. STUDY DESIGN, SIZE, DURATION: Prospective, longitudinal matched cohort study performed in the Fetal Medicine and Obstetric Departments of San Raffaele Hospital in Milan, between 2013 and 2018. The analysis is based on 584 Doppler observations collected from 296 women with different method of conception (OD n = 122; natural conception n = 174). PARTICIPANTS/MATERIALS, SETTING, METHODS: IVF/ICSI viable singleton pregnancies with OD and natural conception control pregnancies matched for BMI and smoking, performing repeated UtA-PI measurements at 11–34 weeks. Miscarriages, abnormalities, twins, significant maternal diseases and other types of ARTs were excluded. Log mean left–right UtA-PI was used for analysis with linear mixed model (LMM) and correction for significant confounders. Pregnancy outcome was also analyzed. MAIN RESULTS AND THE ROLE OF CHANCE: Participants after OD were older and more frequently nulliparous (mean age: OD 43.4, 95% CI from 42.3 to 44.6; natural conception 35.1, 95% CI from 34.5 to 35.7; P -value < 0.001; nulliparous: OD 96.6%; natural conception 56.2%; P -value < 0.001). Mean pulsatility index was lower in OD (UtA-PI: natural conception 1.22; 95% CI from 1.11 to 1.28; OD 1.04; 95% CI from 0.96 to 1.12; P -value < 0.001). A significant effect of parity, gestational age (GA) modeled with a cubic polynomial and BMI was described in the LMM. The mean Log UtA-PI was on average 37% lower in OD as compared to natural conception pregnancies at LMM ( P -value < 0.001). We also found a significant interaction between longitudinal UtA-PI Doppler and GA. Therefore, at 11 weeks' gestation the Log UtA-PI was 42% lower and, at 34 weeks, the differences reduced to 32%. GA at delivery and birth weight were statistically lower in OD group; however, birthweight centile was not statistically different. Preeclampsia was 11-fold more common in the OD group (0.6% and 6.6%, P -value = 0.003). No other significant difference in pregnancy outcome was shown in the study groups (gestational diabetes mellitus, small or large for GA). LIMITATIONS, REASONS FOR CAUTION: It was not possible to properly match for maternal age and to blind the assessment given the major differences between cohorts; however, we did not find significant within-groups effects related to maternal age. Future research is needed to reassess outcomes and correct them for maternal characteristics (e.g. cardiovascular function). WIDER IMPLICATIONS OF THE FINDINGS: This finding reproduces our previous discovery of lower UtA-PI in frozen as compared to fresh blastocyst transfer. The vast majority of OD is obtained by the use of cryopreservation. We speculate that increased uterine perfusion may be the physiological response to compensate dysfunctions both in the mother and in the placenta. STUDY FUNDING/COMPETING INTEREST(S): This is a non-funded study. The authors do not declare competing interest. TRIAL REGISTRATION NUMBER: N/A.